Rapid assessment of pulmonary gas transport with hyperpolarized 129Xe MRI using a 3D radial double golden‐means acquisition with variable flip angles. Issue 6 (22nd April 2018) - Ruppert, Kai; Amzajerdian, Faraz; Hamedani, Hooman; Xin, Yi; Loza, Luis; Achekzai, Tahmina; Duncan, Ian F.; Profka, Harrilla; Siddiqui, Sarmad; Pourfathi, Mehrdad; Cereda, Maurizio F.; Kadlecek, Stephen; et al.
Abstract : Purpose: To demonstrate the feasibility of using a 3D radial double golden‐means acquisition with variable flip angles to monitor pulmonary gas transport in a single breath hold with hyperpolarized xenon‐129 MRI. Methods: Hyperpolarized xenon‐129 MRI scans with interleaved gas‐phase and dissolved‐phase excitations were performed using a 3D radial double golden‐means acquisition in mechanically ventilated rabbits. The flip angle was either held fixed at 15 ° or 5 °, or it was varied linearly in ascending or descending order between 5 ° and 15 ° over a sampling interval of 1000 spokes. Dissolved‐phase and gas‐phase images were reconstructed at high resolution (32 × 32 × 32 matrix size) using all 1000 spokes, or at low resolution (22 × 22 × 22 matrix size) using 400 spokes at a time in a sliding‐window fashion. Based on these sliding‐window images, relative change maps were obtained using the highest mean flip angle as the reference, and aggregated pixel‐based changes were tracked. Results: Although the signal intensities in the dissolve‐phase maps were mostly constant in the fixed flip‐angle acquisitions, they varied significantly as a function of average flip angle in the variable flip‐angle acquisitions. The latter trend reflects the underlying changes in observed dissolve‐phase magnetization distribution due to pulmonary gas uptake and transport. Conclusion: 3D radial double golden‐means acquisitions with variable flip angles provide a robust means for rapidly assessing lung function during a single breath hold, thereby constituting a particularly valuable tool for imaging uncooperative or pediatric patient populations.